Trends in the karyotypic evolution of the Neotropical catfish family Heptapteridae Bockmann 1998 (Teleostei: Siluriformes) - de Borba, Rafael Splendore [UNESP]; da Silva, Edson Lourenco [UNESP]; Sales Pacheco, Ana Carolina [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP]; Alves, Anderson Luis [UNESP] (Springer, 2012)
The Heptapteridae family is endemic to the Neotropics and is one of the most representative members of the Siluriformes order in small bodies of water. Due the lack of data for clearly distinguishing their species, only recently was elevated from condition of subfamily to family. However, many doubts about certain species remain yet. There are a relatively large number of cytogenetics studies about heptapterids that permits comparative analyses focused in the karyotype evolution of the group. However, the absence of studies about this theme motivated this work. Were analyzed cytogenetically most representative species of the family: , and compared with available data from the family. The comparative analysis indicated the predominance of biarmed chromosomes and low variation of the diploid number (around 2n = 58) suggesting that centric inversions were more important than centric fissions in the history of heptapterids. It is corroborated by a remarkable number of NOR phenotypes mainly in and species. A probable condition of Heptapteridae plesiomorphic karyotype would be one composed of 2n = 58 chromosomes of types metacentric and submetacentric mainly, with simple NOR at the sub terminal position. The reduction of diploid number, it would possibly through successive events of chromosome fusion with deletions and inversion rearrangements responsible for NOR variation within the certain genus. The occurrence of B chromosomes is from a derived event, possibly of recent origin, without phylogenetic implications.
Keywords: Chromosome; Karyotypic diversity; Ag-NOR; C-band; 18S rDNA